The glutathione S-transferases : kinetics, binding and inhibition - Goold, Richard David (Division of Medical Biochemistry and Structural Biology, 2018)
The glutathione S-transferases are a group of enzymes which catalyse the conjugation of reduced glutathione with a variety of electrophilic molecules, and they are therefore thought to play a major role in drug biotransformation and the detoxification of xenobiotics. The cytosolic GSH S-transferase isoenzymes of rat, man and mouse have been assigned to three groups, Alpha, Mu and Pi, based on N-terrninal amino acid sequences, substrate specificities, immunological cross-reactivity and sensitivities to inhibitors. The kinetic mechanism of the GSH S-transferases is controversial, due to the observation of non-Michaelian (non-hyperbolic) substrate-rate saturation curves. The most detailed investigations of the steady-state kinetics of glutathione S-transferase have been performed with isoenzyme 3-3 (class Mu) and the substrate 1,2-dichloro-4-nitrobenzene (DCNB). Explanations for the apparently anomalous non-hyperbolic kinetics have included subunit cooperativity, steady-state mechanisms of differing degrees of complexity and the superimposition of either product inhibition or enzyme memory on these mechanisms. This study has confirmed the biphasic kinetics for isoenzyme 3-3 with DCNB and shown non-hyperbolic kinetics for this isoenzyme with 1-chloro-2,4-dinitrobenzene (CDNB) and for isoenzyme 3-4 with DCNB and CDNB. It is proposed that the basic steady-state random sequential Bi Bi mechanism is the simplest mechanism sufficient to explain the non-hyperbolic kinetics of GSH S-transferases 3-3 and 3-4 under initial rate conditions. Neither more complex steady-state mechanisms nor the superimposition of product inhibition or enzyme memory on the simplest steady-state mechanism are necessary.